Are we ready to track climate‐driven shifts in marine species across international boundaries? ‐ A global survey of scientific bottom trawl data. (10th November 2020) - A. Maureaud, Aurore; Frelat, Romain; Pécuchet, Laurène; Shackell, Nancy; Mérigot, Bastien; Pinsky, Malin L.; Amador, Kofi; Anderson, Sean C.; Arkhipkin, Alexander; Auber, Arnaud; Barri, Iça; Bell, Richard J.; et al.
Abstract: Marine biota are redistributing at a rapid pace in response to climate change and shifting seascapes. While changes in fish populations and community structure threaten the sustainability of fisheries, our capacity to adapt by tracking and projecting marine species remains a challenge due to data discontinuities in biological observations, lack of data availability, and mismatch between data and real species distributions. To assess the extent of this challenge, we review the global status and accessibility of ongoing scientific bottom trawl surveys. In total, we gathered metadata for 283, 925 samples from 95 surveys conducted regularly from 2001 to 2019. We identified that 59% of the metadata collected are not publicly available, highlighting that the availability of data is the most important challenge to assess species redistributions under global climate change. Given that the primary purpose of surveys is to provide independent data to inform stock assessment of commercially important populations, we further highlight that single surveys do not cover the full range of the main commercial demersal fish species. An average of 18 surveys is needed to cover at least 50% of species ranges, demonstrating the importance of combining multiple surveys to evaluate species range shifts. We assess the potential for combining surveys to track transboundary species redistributions and show that differences in sampling schemes and inconsistency in sampling can be overcome with spatio‐temporal modeling to follow species density redistributions. In light of our global assessment, we establish a framework for improving the management and conservation of transboundary and migrating marine demersal species. We provide directions to improve data availability and encourage countries to share survey data, to assess species vulnerabilities, and to support management adaptation in a time of climate‐driven ocean changes. Abstract : While many species are changing their spatial distributions rapidly with climate change, the global capacity to track these changes and then adapt management and policy has been limited. To build this capacity for demersal fishes, we compiled the largest worldwide collection of bottom trawl survey metadata and demonstrate how surveys can be combined to follow species across national and survey boundaries. Open data and transparent scientific assessment can be a key step towards improved management of redistributing transboundary species and stocks.